Prevalence of Hypertension in Hemorrhagic Stroke at NGMCTH, Kohalpur - Shrestha, Anil; Shrestha, Richa (Journal of Nepalgunj Medical College, 2018)
Aim: To study the prevalence of hypertension in hemorrhagic stroke in patients admitted in medical units of Nepalgunj Medical College Teaching Hospital (NGMCTH), Kohalpur. Background : Hemorrhagic stroke has remained a serious disease despite recent advances in medical treatment. It is one of the most common emergencies encountered in clinical practice and predominantly effects elderly population leading to chronic disability and dependency. This study was designed to identify hypertension as a major cause of Intracerbral hemorrhage (ICH). Material and methods: This is a cross sectional descriptive study conducted in the department of medicine of NGMCTH, Kohalpur between June 2017 and November 2017. A total of 51 patients were included in the study. History and clinical examinations were recorded. Plain CT scan head, ECG and chest x-ray PA view were done and the data were recorded and analysed. Result: The age of patients ranged from 48 to 89 years with the mean age of 66.72 years. Among 51 patients, high BP at presentation along with ECG showing LVH was seen in 38 patients (74.5%) and chest x-ray PA view showing cardiomegaly was seen in 31 patients (60.8%). Most commonly involved ethinic group was Tharu (45.1%). Conclusion: Hypertension is a major cause of ICH. So, early detection and regular treatment of hypertension with appropriate antihypertensive drugs and life style modification would prevent ICH.